2020
DOI: 10.2967/jnumed.119.238824
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Identifies Predictors of Survival in Patients with Locally Advanced Cervical Carcinoma and Paraaortic Lymph Node Involvement to Allow Intensification of Treatment

Abstract: Introduction: To use positron emission tomography coupled with computed tomography (18 FDG-PET/CT) to identify a high-risk subgroup requiring therapeutic intensification among patients with locally advanced cervical cancer (LACC) and para-aortic lymph node (PALN) involvement. Methods: In this retrospective multicentric study, patients with LACC and PALN involvement concurrently treated with chemoradiotherapy and extended-field radiotherapy (EFR) between 2006 and 2016 were included. A senior nuclear medicine sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In the 1920s, Otto Warburg observed that proliferating ascites tumor cells preferentially performed glycolysis, even in oxygenrich circumstances (6). This seminal finding has been observed in a wide variety of cancers and currently has been exploited clinically using 18F-deoxyglucose positron emission tomography (7). Mechanically, in proliferating tumor cells, glycolysis, instead of pure mitochondrial metabolism, could provide essential intermediates for biosynthetic pathways, such as lipid or nucleotide synthesis (8).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1920s, Otto Warburg observed that proliferating ascites tumor cells preferentially performed glycolysis, even in oxygenrich circumstances (6). This seminal finding has been observed in a wide variety of cancers and currently has been exploited clinically using 18F-deoxyglucose positron emission tomography (7). Mechanically, in proliferating tumor cells, glycolysis, instead of pure mitochondrial metabolism, could provide essential intermediates for biosynthetic pathways, such as lipid or nucleotide synthesis (8).…”
Section: Introductionmentioning
confidence: 99%
“…Positron emission tomography-computed tomography (PET/CT) with 18 F-fluorodeoxyglucose ( 18 F-FDG) is used in staging, treatment planning, and response assessment in locally advanced cervical cancer (LACC) [3,12,13]. 18 F-FDG PET/CT also has a prognostic value and has been used to study recurrence and survival outcome [14][15][16][17]. Metabolic parameters based on the standardized uptake value (SUV), like the highest SUV (SUVmax) of the lesion, and the metabolic tumor volume (MTV) as well as total lesion glycolysis (TLG) have been studied previously.…”
Section: Introductionmentioning
confidence: 99%
“…About 40% of these patients show locally advanced cervical carcinoma (LACC) at initial diagnosis [ 2 ]. The standard treatment for LACC is specific cisplatin-based radiotherapy chemotherapy (CRT) [ 3 ]. However, usually, in 33% of cases, the tumor recurs about 2 years after CRT, and the overall 5-year survival is approximately 70% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for LACC is specific cisplatin-based radiotherapy chemotherapy (CRT) [ 3 ]. However, usually, in 33% of cases, the tumor recurs about 2 years after CRT, and the overall 5-year survival is approximately 70% [ 3 ]. Lymph node status, response to treatment, and clinical stage are the main predictors of recurrence.…”
Section: Introductionmentioning
confidence: 99%